'Inglan is a bitch': hostile NHS charging regulations contravene the ethical principles of the medical profession. Issue 8 (22nd July 2019) - Reynolds, Josephine Mary Katharine; Mitchell, Caroline
Abstract : Following the recent condemnation of the National Health Service charging regulations by medical colleges and the UK Faculty of Public Health, we demonstrate that through enactment of this policy, the medical profession is betraying its core ethical principles. Through dissection of the policy using Beauchamp and Childress' framework, a disrespect for autonomy becomes evident in the operationalisation of the charging regulations, just as a disregard for confidentiality was apparent in the data sharing Memorandum of Understanding. Negative consequences of the regulations are documented to highlight their importance for clinical decision makers under the principles of beneficence and non-maleficence. Exploration of the principle of justice illuminates the core differentiation between the border-bound duties of the State and borderless duties of the clinician, exposing a fundamental tension.